A new blind Lamyctes (Chilopoda: Lithobiomorpha) from Tasmania with an analysis of molecular sequence data for the Lamyctes- Henicops Group - Edgecombe, Gregory D.; Giribet, Gonzalo (Zootaxa, 2003)
The cosmopolitan, parthenogenetic centipede Lamyctes coeculus (Brölemann, 1889), type species of Lamyctinus Silvestri, 1909, occurs in New South Wales and Lord Howe Island, Australia, the former genetically identical to specimens from Tucumán, Argentina. Parsimony analysis of complete sequences of 18S rRNA and fragments of 28S rRNA, 16S rRNA, and cytochrome c oxidase subunit I for the Lamyctes-Henicops group suggests that loss of ocelli in Lamyctes coeculus has an independent origin from blindness in Lamyctes hellyeri n. sp. from northern Tasmania. Lamyctinus is nested within Lamyctes Meinert, 1868, its senior synonym. Lamyctes hellyeri is known exclusively from females in gardens, and is probably introduced to Tasmania.